2005
DOI: 10.1148/radiol.2353040086
|View full text |Cite
|
Sign up to set email alerts
|

US Features of the Normal Appendix and Surrounding Area in Children

Abstract: The results of this study show that a normal appendix can be depicted with US in 82% of asymptomatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
3
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 12 publications
4
43
3
4
Order By: Relevance
“…In our opinion, we must exploit the full potential of USG before considering CT scan as another option. If Wiersma et al [20] could demonstrate a normal appendix in children in 82 % of cases, why can we not identify a pathological appendix? What is really needed today is a dedicated appendiceal USG by an experienced radiologist for suspected cases of AA.…”
Section: Discussionmentioning
confidence: 92%
“…In our opinion, we must exploit the full potential of USG before considering CT scan as another option. If Wiersma et al [20] could demonstrate a normal appendix in children in 82 % of cases, why can we not identify a pathological appendix? What is really needed today is a dedicated appendiceal USG by an experienced radiologist for suspected cases of AA.…”
Section: Discussionmentioning
confidence: 92%
“…The normal appendix can be seen in 82% of asymptomatic children [23]. If the normal appendix can be visualised with US, appendicitis can be safely ruled out.…”
Section: Us or Ct In Children With Suspected Appendicitis?mentioning
confidence: 99%
“…In many cases, therefore, changes associated with abdominal pain may facilitate visualization of the appendix. Wiersma et al [30] found that in pediatric subjects, a normal appendix was depicted more frequently than in adults, possibly because there is less attenuation of the ultrasonic beam by subcutaneous fat and muscle, which are thinner in pediatric subjects [31].…”
Section: Discussionmentioning
confidence: 99%